MODELS OF THE MANTLE SHEAR VELOCITY AND DISCONTINUITIES IN THE PATTERN OF LATERAL HETEROGENEITIES - Gu Y.J.; Dziewonski A.M.; Su W.; Ekström G. (My University, 2001)
Resolution of the pattern of large-scale shear velocity variations above and below the known and postulated mantle discontinuities could provide con- straints on the nature of mineral phase transitions, changes in composition, and the scale of mantle convection. To achieve good resolution across a full range of depths, we use a diversified data set consisting of body and mantle wave waveforms, travel times, and surface wave phase velocities. Our main focus is on the 670-km discontinuity, long presumed to be an important barrier, or impediment, to whole mantle convection. Our data set has a relatively high radial resolution throughout the mantle; in the transition zone and some 200 km below it, the long period wave- forms, dominated by multiple surface reflections, make a particularly important contribution. We use a local spline support to parameterize the model; this allows us to obtain a smooth model (twice differentiable) and simplifies calculation of the model and its derivatives in applications such as three-dimensional ray tracing. In one inversion we use a continuous radial representation throughout the mantle; in the other, a discontinuity is allowed across the 670-km boundary. Both models suggest that the long-wavelength anomalies of the transition zone and the mantle below 750 km are significantly different. Near 670 km these two models display notable differences in the peak amplitudes and lateral scales of major anomalies. The degree 2 spherical harmonic, which dominates the large-scale shear velocities in the transition zone, is strongly attenuated at the top of the lower mantle where the power spectrum is essentially white. Resolution tests show that these results are robust, which suggests a possible reorganization of the flow between the upper and lower mantle. At other depths the power spectra of our models as a function of depth indicate a modest change near 400 km, where the dominating effect of degree 5 (shields) is replaced by degree 2 (slabs). The power of the heterogeneity in at mid-mantle depths is low and nearly fiat as a function of spherical harmonic degree up to g = 12, with no detectable change near 1000 km. The increase of the power in the lowermost mantle is rather gradual, not characteristic of a discontinuous change. Cross sections of our models at major subduction zones indicate that major downwelling of cold slab material may occur at some locations. On the other hand, there are numerous examples of an abrupt change of the sign of the velocity anomalies across the 670-km discontinuity.